The influence of chemical structure of chromophore on polymerization of methacrylic azomonomers - Nadtoka, Oksana; Syromyatnikov, Volodymyr (Publishing House of Lviv Polytechnic National University, 2014)
Methacrylic azomonomers based on paraaminoacetanilide suitable for preparation of liquid crystal (LC) photoaligning functionalized polymers were synthesized. Azofragments include various aromatic rings: benzene, naphthalene, 8-oxyquinoline, and thiazole derivatives. The kinetics of polymerization of synthesized azomonomers was studied. Efficient polymerization constants KS of thermo-induced radical polymerization are presented. The relative activities r1 and r2 were calculated by the Fineman-Ross method. It was shown that the nature of the aromatic ring in azochromofore influences polymerization rate by two ways: steric effect and chemical structure. Thus, structurally coloured (co)polymers based on synthesized monomers were obtained and the absorption spectra of polymer films were recorded. We have used different electron donor and electron-acceptor groups (push–pull effect creation) in rings to enhance absorption and charge transfer properties. The structure–property relationship has been studied, which allowed us to conclude that push-pull effect influences absorption maximum shift of synthesized polymers. Синтезовано метакрилові азомономери на основі пара-аміноацетаніліду, що використовуються для отримання функціоналізованих полімерів для орієнтації рідких кристалів. Азофрагменти містять у своїй структурі різноманітні ароматичні ядра: бензольне, нафталінове, 8- оксихіноліонове та похідні тіазолу. Вивчено кінетику полімеризації синтезованих азомономерів. Представлено сумарні константи ефективності термоінфційованої полімеризації KS. Методом Файнмена-Росса визначено константи кополімеризації та розраховано параметри Q та e. Показано, що природа ароматичного ядра впливає на швидкість полімеризації двома шляхами: через стеричний чинник та безпосередньо хімічну будову. Отримано структурно- забарвлені (ко)полімери на основі синтезованих мономерів, а також записано їх спектри поглинання. Показано, що при використанні електоноакцепторних та електронодонорних замісників (створення пуш-пульного ефекту) можливе посилення як поглинання, так і здатність до перенесення заряду в системі. Вивчено взаємовплив структура-властивості і показний вплив пуш-пульного ефекту на зміну максимуму поглинання синтезованих полімерів.
Вплив хімічної природи хромофора на полімеризаційні властивості метакрилових азомономерів
Keywords: azomonomer; polymerization; monomers reactivity; UV-spectra; азомономер; полімеризація; активність мономерів; УФ-спектри